Cardia and non‐cardia gastric cancer risk associated with Helicobacter pylori in East Asia and the West: A systematic review, meta‐analysis, and estimation of population attributable fraction. Issue 2 (16th January 2023) - Han, Zhongxue; Liu, Jing; Zhang, Wenlin; Kong, Qingzhou; Wan, Meng; Lin, Minjuan; Lin, Boshen; Ding, Yuming; Duan, Miao; Li, Yueyue; Zuo, Xiuli; Li, Yanqing
Abstract: Objectives: To assess the region‐specific relative risk of cardia/non‐cardia gastric cancer (CGC/NCGC) associated with Helicobacter pylori ( H. pylori) and quantify its contribution to gastric cancer burden using population attributable fraction (PAF). Methods: PubMed, EMBASE, Web of Science, and Cochrane Central databases were searched by two reviewers until April 20, 2022. The association between H. pylori infection and NCGC/CGC was assessed using pooled odds ratios (ORs) with 95% confidence intervals (CIs). PAF was calculated using the formula of H. pylori prevalence and the pooled OR. Results: One hundred and eight studies were included. A significant association was observed between H. pylori infection and NCGC in East Asia (OR, 4.36; 95% CI: 3.54–5.37) and the West (OR, 4.03; 95% CI: 2.59–6.27). Regarding CGC, a significant association was found only in East Asia (OR, 2.86; 95% CI: 2.26–3.63), not in the West (OR, 0.80; 95% CI: 0.61–1.05). For studies with a follow‐up time of ≥10 years, pooled ORs for NCGC and CGC in East Asia were 5.58 (95% CI: 4.08–7.64) and 3.86 (95% CI: 2.69–5.55), respectively. Pooled OR for NCGC was 6.80 (95% CI: 3.78–12.25) in the West. PAFs showed that H. pylori infection accounted for 71.2% of NCGC, 60.7% of CGC in East Asia, and 73.2% of NCGC in the West. Conclusions: Gastric cancer burden associated with H. pylori infection exhibits important geographical differences. Prolonged follow‐up period could overcome the underestimation of the magnitude of the association between H. pylori infection and CGC/NCGC. Customized strategies for H. pylori screening and eradication should be implemented to prevent gastric cancer.